Analysis of The Need for The Development of Local-Based English Teaching Materials to Improve Reading Literacy in High School Students - Makhroji Makhroji; Irma Dewi Isda (AL-ISHLAH: Jurnal Pendidikan, 2023)
The teaching materials used are English teaching materials which contain local learning concepts that increase the discussion of how to read English correctly in pronouncing words in accordance with grammar. Therefore, English teaching materials are very useful for students to master reading literacy skills. English is also part of the international language contained in the  subjects applied in schools.   In this case, students  are required to have English teaching  materials as a  guide in mastering English knowledge  and are also able to compete nationally and internationally.    Thus, the purpose of this study was born, namely to determine the analysis of the  need for the development of locally based English teaching materials to improve reading literacy.  This research uses a design research development method that takes the form of a type of study validation. The basis of the use of this type of method  proves from the theory of  learning at the stage of needs analysis. The results  of the study show that  the usefulness of  local learning teaching materials can increase students' reading literacy more independently.  Local learning  teaching materials can make it easier for  teachers to be used as a source of learning media. The conclusion of this study is that local learning teaching  materials can be implemented  for learning activities  and English language learning  is more practical and easy to understand .